Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar IPAS Materi Wujud Zat dan Perubahannya Pada Siswa Kelas IV MI/SD - Marniati Kadir; Lusiana Amanda Lestari; Sheilla Oktaviani (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aimed to improve students' learning outcomes on the topic of states of matter and their changes through the implementation of the Problem-Based Learning model. This classroom action research was conducted in two cycles. The results showed that learning mastery increased from 16.67% in the pre-cycle to 66.67% in Cycle I and 83.33% in Cycle II. The implementation of PBL also improved students’ participation, collaboration, and problem-solving abilities during the learning process.